2023
DOI: 10.17776/csj.1243136
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Nodal Problem for a Conformable Fractional Diffusion Operator With Parameter-Dependent Nonlocal Boundary Condition

Abstract: In this paper, we consider the inverse nodal problem for the conformable fractional diffusion operator with parameter-dependent Bitsadze–Samarskii type nonlocal boundary condition. We obtain the asymptotics for the eigenvalues, the eigenfunctions, and the zeros of the eigenfunctions (called nodal points or nodes) of the considered operator, and provide a constructive procedure for solving the inverse nodal problem, i.e., we reconstruct the potential functions p(x) and q(x) by using a dense subset of the nodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In 2017, Jarad et al [15] showed that this derivative is necessary and useful for generating new types of fractional operators. In recent years, numerous significant studies [16][17][18][19][20] have been conducted on inverse problems related to various conformable fractional operators, including the diffusion operator.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Jarad et al [15] showed that this derivative is necessary and useful for generating new types of fractional operators. In recent years, numerous significant studies [16][17][18][19][20] have been conducted on inverse problems related to various conformable fractional operators, including the diffusion operator.…”
Section: Introductionmentioning
confidence: 99%